Area deprivation and notifiable infectious diseases in Germany: A longitudinal small-area analysis. (13th November 2019) - Rohleder, S; Stock, C; Maier, W; Bozorgmehr, K
Abstract: Background: Socioeconomic inequalities may affect the infectious disease incidence. We studied the association between area deprivation and incidence of notifiable infectious diseases in Germany to understand spatio-temporal patterns and the effects of societal factors on disease epidemiology. Methods: Using national surveillance data of 401 districts from 2001 to 2017, we examined the incidence of infectious diseases using spatiotemporal Bayesian regression models. We analyzed eight disease classes: blood-borne viral hepatitis, gastrointestinal, vaccine preventable, vector-borne, zoonotic, other bacterial, other infectious, and overall burden of infectious diseases. As explanatory factors we considered area deprivation (measured by the German Index of Multiple Deprivation), fraction of non-nationals, sex, age, and spatiotemporal effects. Results: A risk gradient across deprivation quintiles was observed for the overall burden of infectious diseases. The relative risk (RR) for gastrointestinal diseases in areas with medium and high deprivation relative to low deprivation was 1.65 (95%-credible interval [CrI] 1.01-2.54) and 2.64 (1.22-4.98), respectively. The RR for vector-borne diseases was 1.89 (1.27-2.73) in districts with high deprivation compared to areas with low deprivation. Lower risks in highly deprived areas relative to low deprived areas were identified in vaccine-preventable diseases (RR = 0.39; 0.14-0.88) and zoonoses (RR = 0.69; 0.48-0.96). For blood-borne viral hepatitis, other bacterial, and other infectious diseases no association with area deprivation was observed. Spatial risks of infections were predominantly concentrated in eastern parts of Germany and changed marginally over time. Conclusions: The risks of infections tend to be higher in more deprived areas and in eastern parts of Germany, but they varied by class of disease. Our results can guide measures of infectious disease control and prevention by considering spatial risks and deprivation. Key messages: Area deprivation has both positive and inverse associations with the incidences of infectious diseases in Germany. Regions with increased risks may benefit from targeted public health measures. Spatial risks of infections tended to be higher in eastern regions of Germany. Disparities in the incidence of infectious diseases may be still present between western and eastern Germany.